The Design of The Spk in Fulfilling the Production Target of Vegetable Availability in Lut Tawar Sub-District Uses The SAW Method - Rayuwati Rayuwati; Yelli Novelia Putri (International Journal of Management Science and Information Technology, 2021)
Efforts to meet the availability of vegetables in fulfilling vegetable intake, especially for people in Lutawar sub-district, Central Aceh district, community agriculture requires a technology development that supports the calculation of production at each harvest and can also determine the fulfillment of community food availability. In this case, the fulfillment of production targets for the availability of vegetables will be very effective if it is calculated using a decision support system application, using the Simple Additive weighting (SAW) method.The process of collecting and analyzing data is carried out systematically and logically using a survey, which is to collect as much data as possible about the vegetables found in Lut Tawar Subdistrict, which is a decision support for the quality of the research. Then analyze vegetables in meeting production targets and food availability. Application of the Simple Additive Weighting (SAW) method into a decision support system to create a decision support system for food availability that is assessed from its production, including 4 criteria used to make an assessment, C1: Productivity, C2: Harvest Area, C3: Area Planting, C4: Population, then decision making assigns weight to each criterion. The types of vegetables as an alternative in this study are as follows